Solar Powered Transcritical CO2 Cogeneration Plant for the Union Territory of Ladakh, India - Vivek Kumar; Khalid Parra; Uday Raj Singh; Satya Sekhar Bhogilla (Solar Compass)
The transcritical and supercritical CO2 cycles have been gaining significant attention as alternative cycles for power generation. These cycles can be operated with diverse heat sources, such as nuclear, coal, and renewable heat sources, like solar energy. In this work, a concentrating solar power (CSP) plant is proposed as the heat source for the working fluid (CO2) to exploit the high solar potential offered by the Ladakh UT. Chloride-based salt is proposed as the thermal energy storage (TES) media, which can help to achieve high turbine inlet temperatures (700°C), thereby improving thermal efficiency. The manuscript focuses on cogeneration to improve the overall system efficiency. In addition to power generation utilizing a simple recuperated tCO2 Rankine Cycle, the high-temperature turbine exhaust is proposed to provide hot water for space heating using a fourth-generation district heating plant. Thermodynamic analysis of the system for a 10 MW capacity plant suggests a high overall efficiency of 49.75 % is attainable. An increase in the turbine-specific work is observed in the winter season as the ambient temperatures drop due to a reduction in the liquid saturation temperature of CO2. Moreover, a district heating system in line with fourth-generation district heating is recommended, wherein low supply and return temperatures of water will further ensure efficient system performance.